2018
DOI: 10.18619/2072-9146-2017-5-14-17
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGICAL AND REPRODUCTIVE FEATURES OF PHYSALIS spp. IN TEMPERATE CLIMATE

Abstract: Культурные сорта физалиса со съедобными плодами по ботаническим и хозяйственно ценным признакам принадлежат к двум группам -южноамериканской и мексиканской. К южноамериканской группе относятся физалисы с мелкими сладкими ароматными плодами. Это так называемые ягодные физалисы. Из этой группы наибольший ареал занимают P. peruviana L., P. minima, P. pubescens L. Они культивируются в течение продолжительного времени из-за сочных ягод [5]. К мексиканской группе относятся виды физалиса с более крупными, но менее сл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This value is higher than the reported earlier for Russia; for example, some authors reported 3.0-4.5 kg/m 2 [14]. Commercial husk tomato varieties grown in an open field experiment yielded 5.6-6.4 kg/m 2 in New Hampshire, U.S.A. [25]; 1.1-1.9 kg/per plant (similar to our values) in Georgia, U.S.A. [26]; 1.1-2.6 kg/per plant in Mexico [27]; and 1.8 kg/per plant in the European part of Russia [28]. At the same time, husk tomato production in California was reported as ranging from 1.5 to 3.5 t/acre; i.e., 0.4-0.9 kg/m 2 , which is extremely low and even seems to be erroneous [29].…”
Section: Discussionsupporting
confidence: 86%
“…This value is higher than the reported earlier for Russia; for example, some authors reported 3.0-4.5 kg/m 2 [14]. Commercial husk tomato varieties grown in an open field experiment yielded 5.6-6.4 kg/m 2 in New Hampshire, U.S.A. [25]; 1.1-1.9 kg/per plant (similar to our values) in Georgia, U.S.A. [26]; 1.1-2.6 kg/per plant in Mexico [27]; and 1.8 kg/per plant in the European part of Russia [28]. At the same time, husk tomato production in California was reported as ranging from 1.5 to 3.5 t/acre; i.e., 0.4-0.9 kg/m 2 , which is extremely low and even seems to be erroneous [29].…”
Section: Discussionsupporting
confidence: 86%
“…In fact, P. angulatum varieties grown in Brazil (De Souza et al, 2017) showed mean fruit weight of 12 to 14 g, that is 4.5 to 6.5 times lower than those recorded for Russian cultivars, those in our research (Tab. 1) and in other investigations (Mamedov and Engalychev, 2017). Russian P. angulatum varieties are also characterized by twice the number of seeds per fruit (Mamedov and Engalychev, 2017) compared with berries produced by Brazilian P. angulata genotypes (De Souza et al, 2017), which may even affect fruit growth.…”
Section: Yield Quality Indicators and Antioxidantsmentioning
confidence: 70%
“…1) and in other investigations (Mamedov and Engalychev, 2017). Russian P. angulatum varieties are also characterized by twice the number of seeds per fruit (Mamedov and Engalychev, 2017) compared with berries produced by Brazilian P. angulata genotypes (De Souza et al, 2017), which may even affect fruit growth. Further, genotype selection for plant resistance to abiotic and biotic stresses, i.e.…”
Section: Yield Quality Indicators and Antioxidantsmentioning
confidence: 70%